Factors Influencing Classroom Participation: A Case Study of Undergraduate Students at Education Faculty, Paktia University - Rohi, Saifurahman; Muslim, Saifullah (Journal for Research in Applied Sciences and Biotechnology, 2023)
There was a lack of students’ participation in classroom activities. Student participation varied according to gender, education level, housing area, and employment, language proficiency and cultural restrictions. It was needed to discover factors that influence students’ participation in classroom activities, to address the current situation and key challenges of classroom participation. Therefore, the objectives of the study were to distinguish the factors that increase and decrease student classroom participation and to investigate the most influential factors that affect classroom participation. In addition, the research recommends sustainable resolutions. The methodology adopted includes the use of questionnaires, two classes of observation in the English department, and a review of relevant documents. The size of the class, a lack of time, and the course policies that were observed in class were major barriers to student participation in class activities. Teachers did not give students enough time to consider the question before responding. The current survey found that the personalities of the instructor and students, the size of the classroom, and the perception of peers influenced students' willingness to speak up in class. It is pointed out that both active and passive students agree that instructors are the main characters in classrooms. The method or style of teaching and positive traits of instructors play an important role in motivating and stimulating verbal engagement among students in the classroom. Students actively participated when they received an equal chance to participate in the classroom. When there was respect, small classes, student support, constructive feedback, and the application of theory to a real-life situation, participation levels in classes were higher. Moreover, teachers must consider and overcome those factors to give students a chance to communicate effectively in classroom participation.